ANALYSIS OF STUDENTS' LEARNING DIFFICULTIES IN SCIENCE LEARNING IN SMP NEGERI 2 PENDOPO - Tasya Nur Galita; Metra Suraya; Pebrianti Pebrianti; Sopiah Citrawati; Adrian Topano (EDUPROXIMA : Jurnal Ilmiah Pendidikan IPA, 2024)
In the learning process, learning difficulties are a condition of students in receiving lessons that will cause an obstacle in a person's learning process. learning difficulties in children can be seen in the classroom learning process, so this needs to be a major concern in the child's future self-development. The population in this study were all students of class IX SMP Negeri 2 Pendopo. The method used in this research is descriptive qualitative method. This method describes the data obtained through observation of data from the school. From the results of the study most students have difficulty in learning to study science in class. Even some students experience a long delay in the learning process. This is characterized by the inability of students to follow class learning in science learning. Data analysis obtained data that the lowest questionnaire value is in the realm of score 65, namely learning difficulties are at a high level of learning difficulty, then the questionnaire value is in the realm of score 71, namely learning difficulties are at a moderate level, and for the highest questionnaire value is in the realm of score 88, namely the level of learning difficulty is low. Learning difficulties in class IX students of SMP Negeri 2 Pendopo are obtained from many factors both internally which include physiological and external factors which include the social environment.